(untitled) (Purbanchal University Health Journal, 2024)
Introduction: Adolescents is a critical phase in a person’s life as various problems and risk factors may arise in this stage. Bullying refers to actions with aggression that are repeated with an intention to hurt others and create unequal situations. Objective: The objective of the study is to assess the prevalence of bullying among secondary level school students in metropolitan city in Koshi province. Method: A descriptive cross-sectional design was conducted among the secondary level students in 3 school operating in Biratnagar metropolitan city of Koshi Province, Nepal. Multistage sampling technique was used to select the sample of the study. Data was collected through self-administered method using Adolescent Peer Relation Instrument (APRI-B/T) standard tool. Descriptive statistics followed by chi- square test was utilized to explore the relationship between participant’s sociodemographic characteristics and bulling practice. Result: A total number of 345 adolescent students participated in this study, of which majority (87%) had done bullying while 13% were not been involved in bullying behavior. More than two third (72.2%) were engaged in mild bullying while minority (2.6%) were engaged in severe form of bullying. Majority (83.8%) of the students were involved in verbal bullying, (67%) social bullying and (64.6%) physical bullying. There was a significant association between prevalence of bullying with demographic variables like gender (p = 0.04), ethnicity (p = 0.0002), residence (p= 0.003), mother’s education (p= 0.003), school type (p= 0.000), father’s education (p= 0.000) and grade in previous year (p= 0.000). Conclusion: Trends of bullying practice among the secondary level school students in this area were high in domain specifically in verbal bullying. Prevalence of these practice was significantly associated among gender, ethnicity, residence, school factors and parental educations. The study recommends educational awareness and appropriate vigilance programs in schools of these areas to curb bullying practice among teenagers.